Reducing turnaround time in a pathology laboratory using the lean methodology. Issue 3 (28th March 2023) - Akbulut, Yasemin; Usubütün, Alp; Durur, Fatih; Kutlu, Gamze
Abstract : Purpose: The aim of this study is to determine the effect of the application of the lean methodoloy in the pathology laboratory and to evaluate the results on the turnaround time. Design/methodology/approach: This study was a prospective intervention study formed of the three stages of pre-intervention, determination of problem areas and the application of lean techniques and quality improvement. The study was conducted between February 2019 and August 2020. In the first stage, research was made through interviews, observations, questionnaires and seminars; in the second stage, observations, brain-storming, process flowcharts and fishbone diagram were used; and in the third stage, Kaizen, A3 method and spaghetti diagram were applied. Findings: Following the application of lean techniques, turnaround time in the pathology laboratory was decreased, and the changes made in the working methods and placement of the units in the laboratory were found to have prevented unnecessary steps. The lean method was also determined to have had positive effects on the workplace satisfaction of the laboratory employees and of the physicians working with the laboratory. Originality/value: The results showed that applying lean techniques could reduce waste and increase participation in processes. This article demonstrates its originality and relevance by proving that the lean techniques can be applied in the hospital laboratory. Actions to improve turnaround time are also crucial for the efficient use of resources.